Gambaran Karakteristik Pasien Covid-19 dengan Riwayat Penyakit Kardiovaskular di Sebuah Rumah Sakit di Provinsi Jawa Barat - Mochammad Rachmat Deriansyah; Poernomo; Titik Respati (UNISBA Press, 2023)
Abstract. COVID-19 patients who have recovered can experience long COVID, one of the risk factors is comorbidities. Cardiovascular disease is one of the comorbidities of COVID-19. The NICE guidelines and the CDC define long COVID as individuals with symptoms of COVID-19 that persist for more than 4 weeks after first infection. This study aims to determine patient characteristics based on age and gender of COVID-19 patients with a history of cardiovascular disease who experience long-term events of COVID. This research is a descriptive observational study with a cross-sectional design. took place from March – November 2022. Patient data was taken based on medical records and the statistical analysis used was univariate. The results of this study showed that the majority of the 88 patients were mostly in the age range of 60-75 years (45.4%), female (51.1%), and duration of hospitalization <14 days (65.9%) . It can be concluded that the majority of COVID-19 patients are aged 60-75 years, female sex, and are hospitalized <14 days. Abstrak. Pasien COVID-19 yang sudah sembuh dapat mengalami long COVID, salah satu faktor resiko adalah komorbid. Penyakit kardiovaskular merupakan salah satu komorbid dari COVID-19. NICE guidelines beserta CDC mendefinisikan long COVID sebagai individu dengan gejala dari COVID-19 yang persisten lebih dari 4 minggu setelah pertama terinfeksi. Penelitian ini bertujuan untuk mengetahui karakteristik pasien berdasarkan usia dan jenis kelamin dari pasien COVID-19 dengan riwayat penyakit kardiovaskuler yang mengalami kejadian long COVID. Penelitian ini adalah penelitian observasional secara deskriptif dengan rancangan cross-sectional. berlangsung dari Maret – November 2022. Data pasien diambil berdasarkan rekam medis dan analisis statistik yang digunakan adalah univariat. Hasil penelitian ini menunjukkan bahwa mayoritas dari 88 pasien, paling banyak berada di rentang usia 60-75 tahun (45,4%), jenis kelamin perempuan (51,1%), dan durasi rawat inap <14 hari (65,9%). Dapat disimpulkan bahwa mayoritas pasien COVID-19 berusia 60-75 tahun, jenis kelamin perempuan, dan dirawat <14 hari.